TikTok Usage Intensity and Its Impact on Students' Learning Motivation and Discipline - Rachmasari, Milandia Nur; Narimo, Sabar (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
This study aims to analyze the Influence of TikTok use intensity on students' motivation and learning discipline at Muhammadiyah Purwodadi High School. This study uses a quantitative, correlational, associative Research design and involves 107 grade XI students of SMA Muhammadiyah Purwodadi as the sample, selected through a proportional random sampling technique from a total population of 145 students. Data collection is carried out by disseminating questionnaires that have been tested for validity and reliability. Data were analyzed using simple linear regression, t-test, and determination coefficient (R2) with the help of SPSS 24. The study found that the intensity of TikTok use did not significantly affect students' learning motivation or learning discipline. The significance values for learning motivation and learning discipline were 0.693 and 0.346, respectively, the adjusted R-squared values were -0.008 for learning motivation and -0.001 for learning discipline, indicating almost no contribution of the variables. These findings are different from several previous studies that showed a significant Influence of TikTok on motivation and learning discipline.